Habitat induced mutational effects and fatty acid profile changes in bottom dweller Cirrhinus mrigala inhabitant of river Chenab - B. Hussain; T. Sultana; S. Sultana; Z. Iqbal; S. Nadeem; S. Mahboob (Grasas y Aceites, 2015)
Fish from the river Chenab were analyzed for DNA damage by the Comet and Micronucleus assays. The fatty acid profile was determined by gas chromatography using a Flame Ionization Detector. Atomic absorption spectrophotometry showed significant (p < 0.05) levels of contamination due to Cd, Hg, Cu, Mn, Zn, Pb, Cr, Sn and phenols in the fish habitat. The Comet assay revealed significant (p < 0.05) DNA damage in Cirrhinus mrigala of 37.29±2.51%, 34.96±2.53% and 38.80±2.42% in the comet tail, in the tail moment of 23.48±3.90, 19.78±4.26 and 14.30±1.82, in the olive moment of 16.22±2.04, 13.83±1.96 10.99±0.90, respectively, from three experimental sites. The micronucleus assay showed a high frequency of single micronucleus induction of 44.80±3.73, double induction of 06.20±0.97 and nuclear abnormalities of 09.60±1.72, as calculated in a thousand cells. C8:0, C12:0, C20:0, C16:1(n-7), C16:1(n-9), C20:1(n-9), C18:2(n-6), C18:4(n-3), C20:5(n-3), C22:4(n-6) fatty acids were found missing in the fish with a higher intensity of DNA damage but were found in optimal amounts both in farmed and wild fish from non polluted habitats. A highly significant (p < 0.01) correlation was also found in saturated, unsaturated fatty acids and DNA damage and habitat. The present study revealed that the habitat of even lower intensity pollutions not only induce DNA damage but also confiscate essential fatty acids of the omega series and reduce the amount of unsaturated fatty acids for which fish is preferred over other animals.